Impact of Synthesis Method on Phase Transformations of Layered Lithium Vanadium Oxide upon Electrochemical (De)lithiation. Issue 4 (1st January 2019) - Zhang, Qing; Yue, Shiyu; Quilty, Calvin D.; Li, Jing; Zou, Shihui; Stach, Eric A.; Dooryhee, Eric; Takeuchi, Kenneth J.; Takeuchi, Esther S.; Wong, Stanislaus S.; Marschilok, Amy C.
Abstract : Li1.1 V3 O8 (LVO) has shown promise as a cathode material for lithium-based batteries due to its high theoretical capacity (360 mAh . g −1 ) and good rate capability; however, LVO batteries suffer from capacity fade upon extended cycling. The impact of synthetic material control on electrochemistry and capacity retention was explored through solvothermal synthesis of LVO fibers and sol-gel synthesis of LVO rhombohedrons. Cyclic voltammetry (CV) of the two materials revealed key differences where lithiation of the solvothermal-derived LVO material resulted in less β phase formation as compared with the sol-gel-derived material. Structural evolution of the materials during lithiation was characterized through in situ XRD which revealed that the α→β phase conversion is essentially complete in the sol-gel product with only partial conversion in the solvothermal product. Under galvanostatic cycling, the sol-gel product delivered higher capacity but displayed more capacity fade as compared to the solvothermal product as foretold by both CV and XRD findings. When cycled within the α phase region, improved preservation of both energy delivery and structural integrity was observed. These findings substantiate the proposed cause of capacity degradation as originating from an α→β structural change and illustrate the possibility of minimizing β phase formation through synthetic control of LVO.